PREVALENCE OF INTEGRATIVE AND COMPLEMENTARY PRACTICES IN PATIENTS UNDERGOING ANTINEOPLASTIC CHEMOTHERAPY - Isabela Oliva Gurgel; Paola Miranda de Sá; Paula Elaine Diniz dos Reis; Mariângela Leal Cherchiglia; Ilka Afonso Reis; Ana Lúcia de Mattia; Giovana Paula Rezende Simino (Universidade Federal do Paraná, 2019)
Objective: To analyze the prevalence of integrative and complementary practices in patients undergoing antineoplastic chemotherapy. Method: A quantitative, observational, cross-sectional study was conducted at a Chemotherapy Outpatient Unit of a university hospital in Belo Horizonte, Minas Gerais. The sample consisted of 70 patients with data obtained between October 2017 and May 2018. Data were analyzed using the SPSS program through descriptive and inferential statistics. Results: The predominant cancers were breast and colon/rectal. The prevalence of integrative practices was 77.1%, with spirituality being the most used. The funding for the practices was predominantly not provided by the Brazilian Nation Health System. No associated factors were found regarding the use of integrative practices.Conclusion: The patients reported benefits of using integrative complementary practices. It is relevant that nurses know the prevalence of their use and have knowledge to indicate or contraindicate them, when necessary.